Meta-Ethical Remarks against the Proposal of a Normative Model of Leadership Ethics - Duchliński, Piotr (Roczniki Filozoficzne, 2025)
In his critical remarks, I focuses on the following issues: 1) the problem of justifying the necessity of creating a new detailed ethics, 2) the object of study of leadership ethics, 3) the theory of man (anthropology) assumed by the author of the book, 4) the issue of supererogation of acts in the star-shaped model. With many of the solutions that the author of Leadership Ethics proposes, I personally agree. Therefore, the following reflections will not be a form of classical polemics with the author. On the basis of reading the work, some thoughts arose for me regarding more how I, from my point of view, would analyze certain problems concerning leadership ethics that were described by the author. Therefore, my text will not be a form of criticism or an attempt to correct the author’s position, for the reason that in very many places, as I pointed out, I agree with his position. Instead, it will be an attempt to draw attention to certain issues that can be discussed so that the proposed model gains clarity.